THE EFFECT OF COMPENSATION, MOTIVATION, AND WORK SATISFACTION ON OJEK ONLINE DRIVER PERFORMANCE IN SURABAYA - Muhammad Kafid; Bayu Airlangga Putra (NAROTAMA UNIVERSITY, 2019)
The purpose of this study is to analyze the Influence of Compensation, Motivation, and Job Satisfaction on the Performance of Surabaya Regional Ojek Drivers Online. With a sample of 100 respondents. This research is quantitative and data collection through questionnaires and observations. Data analysis used is validity test, reliability test, classic assumption test, and multiple linear analysis test. The results showed that the Influence of the Effect of Compensation, Motivation, and Job Satisfaction on the Performance of Surabaya Regional Ojek Drivers on positive and significant results. The f test results were known at 214,590> f table 17,354 simultaneously. Partially compensation amounted to .211 t table 3,985 Significant effect on motivation of .119 t table of 2.689 has a significant effect on employee performance and job satisfaction of .253 t table 4.194 has a significant effect on employee performance